La Scuola di Mons : Tradizione e attualità dell'arte belga - De Micheli, Mario; Cargnoni, Fausto; Banzola, Maurizio; Rivadossie, Giuseppe; Associazione Artistie Bresciani, Brescia (Milano : Vangelista editore, 1989)
Ensor, James ; Spilliaert, Léon ; Van den Berghe, Fritz ; Permeke, Constant ; Carte, Anto ; Devos, Léon ; Rops, Félicien ; Paulus, Pierre ; Masereel, Frans ; Camus, Gustave ; Somville, Roger ; Landuyt, Octave ; Vandycke, Yvon ; Aubry, André ; Josse, Dany ; Rinchon, Bernard ; et al.
Associazione Artisti Bresciani, Brescia, 28 ottobre - 26 novembre 1989
kunstcatalogus
Keywords: België